Travel Writings on Asia Curiosity, Identities, and Knowledge Across the East, c. 1200 to the Present - Mueller, Christian; Salonia, Matteo (Palgrave Series in Asia and Pacific Studies, 2022)
This open access book provides an analysis of human actors and their capacity to explore and conceptualise their own agency by being curious, gathering knowledge, and shaping identities in their travel reflections on Asia. Thus, the actors open windows across time to present a profound overview of diverse descriptions and constructions of Asia. It is demonstrated that international and transnational history contributes to and benefits from analyses of national and local contexts that in turn enrich our understanding of transcultural encounters and experiences across time. The book proposes an actor-centred contextual approach to travel writing to recount meaningful constructions of Asia's physical, political and spiritual landscapes. It offers comparative reflections on the patterns of encounter across Eurasia, where from the late medieval period an idea of civilisation was transculturally shared yet also constantly questioned and reframed. Tailored for academic and public discussions alike, this volume will be invaluable for both scholars of Global History and interested audiences to stimulate further discussions on the nature of global encounters in Asia.